Bilingual Literacy Among Deaf and Hard-of-Hearing Students: A Literature Review in the USA, Canada, and Colombia - Velásquez Hoyos, Angela Patricia; Jaramillo, Sara; Montoya, Juan Diego (Colombian Applied Linguistics Journal, 2025)
This paper presents a review of the literature on bilingual literacy in deaf and hearing-impaired students in Latin America, the United States, and Canada. The documents selected for this study included undergraduate and graduate thesis projects, governmental documents, and published academic articles. The review indicates that when deaf and hard-of-hearing students learn a second language, it contributes to their professional, academic, and personal growth, enabling them to interact more effectively with people from diverse social and cultural backgrounds. However, the literature also highlights that deaf students face difficulties when entering the educational system, as there are not enough certified bilingual teachers in these countries to instruct this population in sign language. Additionally, the findings suggest that the role of parents is crucial in supporting the learning process of deaf students; thus, a close relationship between schools and families is essential to better assist students with hearing disabilities.